Synthesis of Six- and Seven-Membered Chloromethyl-Substituted Heterocycles via Palladium-Catalyzed Amino- and Oxychlorination - Manick, Anne-Doriane; Berhal, Farouk; Prestat, Guillaume (Synthesis, 2016)
The synthesis of six- and seven-membered chloromethyl-substituted heterocycles, such as piperazinone, tetrahydroquinoxaline, benzodiazepinone, and benzoxazepinone, is reported using palladium-catalyzed vicinal diheterofunctionalization of nonactivated alkenes. The reaction conditions for this domino process are soft and mild, and the chloromethyl appendage allows various post-functionalizations via simple nucleophilic substitutions.
Keywords: palladium; domino reaction; heterocycles; amination; halogenation